Implementation of a National Marine and Fisheries Community Empowerment Program in Aquaculture Businesses in Cilacap - Pola Sabar Tumohon Panjaitan; Catur Pramono Adi; Aripudin; Muhammad Yusuf; Nurhaidin; Mohammad Ismail; Taufik Hadi Ramli (Postgraduate, University of Mataram, 2025)
This study aims to analyze the implementation of the PNPM-MKP-DJDJPB PUMP program, particularly in Cilacap City, assesses public response to the program, and identify factors influencing its implementation. Data analysis was conducted descriptively. The results indicate that while the implementation of the PNPM-MKP program adheres to normative guidelines at each stage, there is a gap between the intended goals and the actual outcomes. This discrepancy is highlighted by public responses regarding program sustainability, participation, benefits, and conflicts during implementation. Additionally, several factors affecting the program’s overall effectiveness were identified, indicating the need for significant improvements. Key supporting factors include the appropriateness of the location, the provision of production equipment, and accuracy in selecting beneficiaries. On the other hand, inhibitory factors include the lack of ongoing support, insufficient training, and misalignment between beneficiary needs and program objectives. Based on these findings, policy recommendations to enhance future direct cash assistance (BLT) programs include: (1) ensuring procedural consistency in program activities, (2) improving beneficiary selection accuracy, (3) providing continuous training and mentoring for beneficiaries, and (4) evaluating the programs to support sustainable business development and beneficiary self-reliance.